SDBL-Prodeo (Self-Directed Belended Learning-oriented Prodeo) Design and Validation to Improve Digital Literacy Chemistry Teacher Candidate Students - St Hayatun Nur Abu; Abd. Rasyid Saraha; Fitriani Ibrahim (EduLine: Journal of Education and Learning Innovation, 2022)
The influence of advances in information and technology causes changes in all aspects of life, including aspects of education or teaching. The ease of accessing digital or internet information through search engines such as Google should be able to be used properly in the learning process and can make students become independent and creative learners. In fact, the condition of students, especially chemistry education students, has not utilized digital resources properly, therefore it is necessary to increase digital literacy for prospective teacher students as their provision to become professional teachers, technology literate and according to the demands of the times. Digital literacy is a skill that not only involves the ability to use technology, information, and communication devices, but also social skills, learning skills, and having attitudes, critical thinking, creative, and inspirational as digital competencies. These abilities can be developed if educators apply innovative learning strategies and are based on the learning independence of students. This study aims to design and validate the Prodeo-oriented Self-Directed Belended Learning (SDBL) (Video Project) or SDBL-Prodeo learning model that can improve the digital literacy of prospective teacher students. The components of the learning model developed consist of a description of the model, theoretical basis, syntax, reaction principle, social system, instructional impact, supporting impact. The SDBL model is an integration of the Self-Directed Learning (SDL) model with Belended Learning. This proposal is a development of previous research that has known the effect of learning chemistry through the creation of videos and images based on social media. The method in this research is RnD research following the 4D development pattern (Define, Design, Development, Disseminate). This research is limited to the development stage, namely the revision of the validation results. The results of the validation of the SDBL-Prodeo model design are in the valid category, which means that the SDBL-Prodeo model can be applied to chemistry learning which aims to improve students' digital literacy.